Strategy Of Online Marketing For Products By Autism Café Project Malaysia - Ahidin, Udin; Kasmad, Kasmad; Arianto, Nurmin (Unpam Press, 2024)
Marketing online has become an important aspect in any business, including the food industry. With the risee-commerce and social media, food companies must develop marketing strategies online strong to remain competitive in the market. The problem formulation How do employees understand efforts, How to market processed food products ffectively. This Community Service was held by proposing material